Research on Staffing Industrial Enterprise Operation in Unstable Market Conditions - I. M. Kublin; N. A. Ivanova; E. G. Dorozhkina; T. A. Andreeva (Вестник Российского экономического университета имени Г. В. Плеханова, 2024)
Production and economic situation observed in product manufacturing makes the problem of personnel management even more topical in view of needs in highly-qualified labour resources. The article provides analysis of HR condition at the industrial enterprise. The analysis is based on statistical data and information collected within the frames of personnel policy monitoring. Certain aspects of HR policy were compared with regard to attracting labour personnel into production sphere at modern industrial enterprise. Challenges of upgrading HR policy were studied with due regard to professional suitability. Special attention was paid to the necessity to implement the program of advanced training based on requirements of production and gathered experience.